Chronic total occlusion in an infarct‐related coronary artery and the risk of appropriate ICD therapies. (4th August 2017) - Di Marco, Andrea; Anguera, Ignasi; Teruel, Luis; Muntane, Guillem; Campbell, Niall G.; Fox, David J.; Brown, Benjamin; Skene, Chris; Davidson, Neil; Leon, Valentina; Dallaglio, Paolo; Elzein, Hind; et al.
Abstract: Introduction: Risk stratification for ventricular arrhythmias in patients with ischemic cardiomyopathy needs to be improved. Coronary chronic total occlusions in an infarct‐related artery (IRA‐CTOs) have been associated with an increased arrhythmic risk. This study aimed to evaluate the association between IRA‐CTOs and appropriate implantable cardioverter‐defibrillator (ICD) therapies. Methods and results: Observational cohort study that included 342 patients with ischemic cardiomyopathy, an ICD implanted for primary or secondary prevention, and a coronary angiography performed shortly before ICD implantation. The ICD was implanted for primary prevention in 163 patients (48%). IRA‐CTO was found in 161 patients (47%). During a median follow‐up of 33 months, 41% of patients experienced at least one appropriate ICD therapy. Patients with IRA‐CTO had higher proportions of appropriate ICD therapies (57% vs. 26%, P < 0.001) and appropriate ICD shocks (40% vs. 17%, P < 0.001). At multivariate Cox regression, IRA‐CTO was the only variable that consistently resulted as independent predictor of appropriate ICD therapies and shocks both in the global population of the study (HR 2.3, P < 0.001 and HR 3, P < 0.001, respectively) and when analyzing separately patients with primary or secondary prevention ICD. Conclusions: IRA‐CTO is an independent predictor of appropriate ICD therapies, including appropriate ICD shocks. This association is consistent across all the subgroups analyzed. Patients with IRA‐CTO have a very high risk of appropriate ICD therapies. These findings may help improving risk stratification as well as the management of ventricular arrhythmias in patients with ischemic cardiomyopathy.